Enhancing Patient Satisfaction Through Web-Based Registration and SEM Analysis of Service Quality Dimensions - Muh Asri; Kifayah Amar; Sapta Asmal (Advance Sustainable Science Engineering and Technology, 2026)
A hospital that provides a wide range of healthcare services must prioritize the satisfaction of patients. Although many studies in Indonesia and Southeast Asia have examined factors influencing patient satisfaction, there is still limited empirical evidence that integrates the role of trust as a mediating variable using a comprehensive service quality model in the hospital context. This study aims to determine the service quality characteristics that influence patient satisfaction at Makassar City Regional General Hospital in Indonesia. Surveys were used to gather data from respondents, consisting of inpatients or their relatives aged 17 years or older, with a total of 300 samples. The data was analyzed using Structural Equation Modeling (SEM), which allows simultaneous testing of complex relationships among latent variables and provides robust estimates for both direct and indirect effects. The study's findings revealed that: (1) Trust was positively influenced by medical personnel attitude, medical services, and nursing care, with P values of 0.033, 0.000, and 0.012, respectively; (2) Trust had a positive effect on patient satisfaction, with a value of 0.000; and (3) Administrative procedures and tangible aspects did not positively affect trust, with P values of 0.345 and 0.106. To improve hospital services, particularly the administrative tasks, a web-based patient registration tool was created. In addition, the availability of ATMs should be considered to enhance tangible evidence indicators. The findings imply that hospital management should focus on strengthening the interpersonal and technical competencies of medical personnel while redesigning administrative systems to be more efficient and patient-friendly, as these factors ultimately drive trust and satisfaction levels.